Positives and Negatives of Distance Education from the Perspective of Teachers with Practical Experience - Sirotová, Mariana; Pieš, Lukáš (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
The COVID-19 pandemic had overnight affected all areas of traditional life. In the field of education, the classic face-to-face teaching was replaced by distance education at all levels of the educational system not only in Slovakia but in all countries of the world. Teachers, pupils, parents, teaching assistants, special educators or professional staff had had no experience with distance education up to that point. In today’s vulnerable world, the possibility of a combined educational process, in which teaching would be divided between face-to-face and distance education, is being raised more frequently mainly in connection with the energy crisis. Setting the right balance between face-to-face and distance education requires, among other things, defining the positives and negatives of these forms. Given the existing extensive theoretical elaboration of the issue of face-to-face teaching, our study focuses on the positives and negatives of distance education, while using the period of the COVID-19 pandemic. Through interviews, we collected the views of primary school teachers experienced in distance education. We focused on questions dealing with advantages, disadvantages, forms, methods and overall attitudes towards distance education. The study concludes by categorising the advantages and disadvantages of distance education. Based on the analysis of the responses obtained through semi-structured interviews with six teachers, we found that distance education has more negative than positive aspects. The main negatives include the lack of physical contact and the absence of social interaction. Furthermore, we found that there is low motivation, skipping lessons and lack of attention among upper grade students. Parental support for pupils in the upper grades was rather low. Teachers mainly used Slovak online platforms for distance learning. This study was done in Slovakia.